SAT0130 Toxic psychosis related with hydroxychloroquine. (1st June 2001) - Barbosa, P; França, M; Almeida, I; Farinha, F; Vasconcelos, C
Abstract : Background: Hydroxychloroquine is one of the commonest antirrheumatic drugs, being well tolerated and traditionally safe. Objectives: Methods: The authors report a case of a 52-year-old woman with a 8 week symmetric polyarththritis, involving the hands, feet, knees and elbows and morning stiffness lasting for more than 60 min. The rheumatoid factor was positive and the X-rays findings were normal. At the time of the first appointment she already had been treated with different NSAID without clinical improvement. Initially we tried low dose steroids only achieving a slight improvement of the patient´s complaints. At the same time, we noticed an enlarged, tender thyroid gland, presenting high T3 and T4 values, low TSH value and positive anti-thyroid antibodies. She initiated specific therapy. Results: Facing a progressive polyarthritis, hydroxychloroquine was started in a 400 mg/d dose. Four weeks later the patient was referred to our out-patient clinic with the following complaints: insomnia, nervousness, incapacity of accomplish her routine daily work, and a fixed idea of general dislike towards her simultaneously with the feeling that everyone´s around was looking at her in a strange way. Hydroxychloroquine was immediately stopped and 72 h later her behaviour was back to normal. Conclusion: We strongly believe that the psychiatric symptoms above were related with the hydroxychloroquine therapy.